The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3892/ijmm.2018.3547
|View full text |Cite
|
Sign up to set email alerts
|

CFTR ameliorates high glucose-induced oxidative stress and inflammation by mediating the NF-κB and MAPK signaling pathways in endothelial cells

Abstract: Diabetic cardiovascular diseases are characterized by progressive hyperglycemia, which results in excessive production of oxidative stress and pro-inflammatory cytokines. Cystic fibrosis (CF) is characterized by chronic inflammation due to mutations in CF transmembrane conductance regulator (CFTR). However, little information is available about the role of CFTR in hyperglycemia‑induced endothelial cell oxidative stress and inflammation. In the present study, a high glucose‑treatment was applied in human umbili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 33 publications
1
18
0
1
Order By: Relevance
“…In type 2 diabetic mice, stimulation of PAR-2 can upregulate TNF-α expression [35]. MAPK and NF-kappa B signalling pathway are associated with the inflammation progress in endothelial cells [36]. Therefore, we examined the expression of TLR4 and TNF-α and MAPK and NF-kappa B signalling pathway-associated protein when PAR-2 on mouse brain microvascular endothelial cell was stimulated by tryptase.…”
Section: Discussionmentioning
confidence: 99%
“…In type 2 diabetic mice, stimulation of PAR-2 can upregulate TNF-α expression [35]. MAPK and NF-kappa B signalling pathway are associated with the inflammation progress in endothelial cells [36]. Therefore, we examined the expression of TLR4 and TNF-α and MAPK and NF-kappa B signalling pathway-associated protein when PAR-2 on mouse brain microvascular endothelial cell was stimulated by tryptase.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we further investigate if other ion channels participate in PA-induced endothelial dysfunction. CFTR is an ATP-gated Cl − channel, and downregulation of CFTR causes apoptosis via ROS and inflammation in renal cells, vascular smooth muscle cells, and other cell types [ 23 , 38 40 ]. In this study, we found that CFTR expression decreased in PA-insulted endothelial cells; Forskolin significantly inhibited PA-induced endothelial dysfunction showing as increasing cell viability, inhibiting cell apoptosis, reducing ROS generation, and restoring NO generation.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies showed that CF patients had endothelial perturbation and microvascular dysfunction [ 15 20 ], suggesting that CFTR deficiency contributes to endothelial dysfunction. Besides, CFTR was showed to protect against endothelial apoptosis from oxidative stress and inflammation [ 21 23 ]. Recently, several researches demonstrated that CFTR regulated autophagy in the intestinal cancer cells, lipopolysaccharide-induced acute lung injury, and the immune response in CF [ 24 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…RelA/p65, c-Rel and RelB, plays a critical role in inflammatory process and metabolic disease [18]. It has been reported that high blood glucose, urinary albumin, angiotensin II could contribute to NF-kappaB activation [19,20]. Evidence have shown that NF-kappaB activation in endothelial cells exerted a vital role in DN.…”
Section: Discussionmentioning
confidence: 99%